Maternal health services utilization among rural Tamang women: A cross sectional study in Nuwakot district of Nepal - Kshitij Karki; Devendra Raj Singh; Sushmita K.C; Sarmin Lama (Al Ameen Medical College, 2019)
Background: Maternal mortality is still a major health issue in Nepal. It is higher among disadvantaged and illiterate women living in rural areas. The major reasons for deaths are low and inequitable utilization of maternal health services. The study aims to assess the utilization of the maternal health services among mothers having under five years children of Tamang community. Methods: A cross-sectional study design was used for the study. A total sample of 139 mothers having under five-year children from Tamang community were selected purposively. Participant mothers were interviewed using semi-structured questionnaires. The study was approved from Nepal Health Research Council and written consent was also taken from the participants prior to data collection. Data was coded, entered in Epidata 3.1v, then transferred to SPSS v20 software and analyzed. Results: The average age of the mothers was 27 years and nearly half of the mothers were illiterate. Among 92.8% of the mothers who had come for Antenatal Care (ANC) checkup, only 57.4% had completed four ANC checkups. Similarly, more than two third (70.5%) of mothers had delivered their child at health institution. On the other hand, only 51.8% of mothers had visited for PNC checkup where only 47.2% of them had 3 PNC checkups. Conclusion: The study revealed that though mothers had visited for ANC and PNC checkups, complete visits were found to be very low. It is recommended to aware the mothers and health care providers on maternal health services and its utilization.